The Role of Canvassers in the Elections in Samut Songkhram Province - พุ่มพวง วรลักษณ์; วันทะนะ สมเกียรติ (Thai Interdisciplinary and Sustainability Review, 2019)
This research aimed to study the concepts and methods that the canvassers used to help the candidates in favour of election campaigns in Samut Songkhram province, by applying quantitative research methodology and questionnaires to collect data from Samut Songkhram canvassers, sample group of 246 individuals, and analyse using computer statistical to describe the result in accordance with the objectives. The results showed that the concepts and methods the canvassers favoured in order to help the candidates the most were cash, promoting the candidates’ past good deeds, and advertising their developmental policies, respectively, whereas the least was providing food/drinks to the voters, to raise popularity for their candidates.